Introduction: On the ethics of debt - William H. Carter; Kate Padgett Walsh (Finance and Society, 2015)
This special issue stems from a 2015 conference on the 'Ethics of Debt', organised by the guest editors and held at Iowa State University. Three themes emerged from the conference and are represented in the articles and documentary film selected for the special issue. The first concerns representations of debt in art and literature. The second theme demonstrates how debt arises and functions in specific contexts. The final theme addresses moral and ethical responses to debt within society.
Keywords: 300